Evaluation the recipient-consumer is an effective manipulative tool influencing the buyer (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
This thesis makes an attempt to define and describe the basic communicative pragmatic features of modern advertising. Advertising communication tends to shorten the use of the language means. This characteristic explains the deliberate usage of such linguistic constructions that primarily influence the potential consumer. The role of advertising has increased in the modern world. Its strengthening intensifies the interest in the study of this social phenomenon among the scientists in various fields. The relevance of the study is obvious due to the fact that the issues of verbal influence on the recipient remains unexplored in modern Ukrainian linguistics.Advertising is a special kind of mass communication, mainly oriented to persuade, influence or force the recipient to choose (buy) the object of advertising. The important communicative feature of the advertising text is that it informs the potential customer about new products / services, and in the same time it mainly aims to implement the pragmatic setup to buy or use the advertising product. This research demonstrates the schematic model of a communicative act between the sender of the advertising message and the recipient. It also defines the basic communicative characteristics of advertising texts. According to the content advertising messages can be distinguished into 3 types: specific, pragmatic and convincing texts. As for the way of information presenting advertising messages are divided into clear and concise texts. The main form of advertising texts is commercial ads with informative, convincing and reminding functions. Such texts get the status of the advertising information subtype in the system of functional styles.Evaluation of the advertised goods / services (both direct and hidden) is an effective communicative pragmatic tool influencing the buyer. The direct assessment of advertised objects is formed by means of rationalistic and sense perceptive absolute variation. The latent assessment is provided by evaluation the recipient-consumer, manipulative formulas and word-concepts. The thesis represents the productivity of using the language means influencing the addressee in advertising texts.
Keywords: advertising; advertising communication; advertising text; manipulation; language means of influence; evaluation